Chemical complementarity between tumor resident, T-cell receptor CDR3s and MAGEA3/6 correlates with increased melanoma survival: Potential relevance to MAGE vaccine auto-reactivity. (October 2022) - Eakins, Rachel A.; Chobrutskiy, Andrea; Teer, Jamie K.; Patel, Dhruv N.; Hsiang, Monica; Huda, Taha I.; Zaman, Saif; Sexton, Wade J.; Coppola, Domenico; Falasiri, Shayan; Blanck, George; Chobrutskiy, Boris I.
Abstract: Cancer testis antigens have been of interest as possible targets for cancer immunotherapies. To better understand the opportunities for the use of such immunotherapy targets, we used a chemical complementarity scoring algorithm and an original web tool to establish aspects of electrostatic complementarity of the CTAs, MAGEA3 and MAGEA6, with melanoma specimen resident, T-cell receptor (TCR) complementarity determining region 3 (CDR3) amino acid sequences. Greater electrostatic complementarity between T-cell receptor CDR3 and tumor CTAs MAGEA3/6 was associated with a greater probability of overall survival, for both the cancer genome atlas and Moffitt Cancer Center samples; and was associated with high levels of T-cell cytotoxicity-related gene expression. Most importantly, this approach allowed for the highly efficient screening of specific segments of the MAGEA3/6 antigens which indicated that certain MAGE segments would have either more or less risk of auto-reactivity. In sum, the chemical complementarity algorithm, and its efficient application via the web tool, adaptivematch.com, offers a convenient opportunity to identify likely parameters important for immunotherapy considerations and melanoma patient risk stratifications. Highlights: Linkage of melanoma immune receptor chemistry to cancer testis antigens and survival. Use of a novel web tool for assessing candidate antigens. Immunogenomics dissections of previously failed vaccines, to identify better candidates.